Governing the "Golden Age of Infrastructure": Assessing Transparency Innovations in Philippine Infrastructure Development. Issue 2 (1st June 2020) - Mendoza, Ronald U.; Cruz, Jerome Patrick
Abstract : Amidst rising infrastructure investment across the Asia‐Pacific, glaring accountability deficits have raised questions about governments' capacity to contain corruption in infrastructure development in the region. Recent developments in the Philippines, however, indicate the presence of challenges related to the ability of digitally enhanced transparency measures to bridge such accountability deficits. This article presents the shifting emphasis in transparency and accountability reforms related to Philippine infrastructure development beginning from the 1990s and assesses transparency innovations under the Duterte administration. While milestone measures such as the establishment of an electronic freedom of information (eFOI) platform have provided convenient access to public information, major hurdles remain in obtaining critical documents concerning infrastructure projects. As borne out in an exercise to request the feasibility studies of 48 flagship infrastructure projects, access to information is still obstructed by factors ranging from technical constraints, uneven service delivery, coordination failures, as well as active legal restrictions against the public's right to know. Abstract : 治理"基础设施的黄金时代"：评估菲律宾基础设施发展中的透明度创新: 在亚太地区基础设施投资不断增加的过程中，明显的问责赤字现象对有关该地区政府在遏制基建设施发展中产生的腐败的能力提出了疑问。然而，近几年菲律宾的发展出现了一系列挑战，后者有关于用经过数字提升的透明度措施填补问责赤字。本文呈现了与自20世纪90年代以来菲律宾基础设施发展相关的透明度和问责改革的变化重点，并评价了杜特尔特政府下的透明度创新。尽管例如建立信息自由电子平台等里程碑式的措施提供了便捷的公众信息获取方式，但主要障碍仍然是获取有关基础设施计划的关键文件。正如一项要求获取48个标志性基础设施计划的可行性研究的实践所证明的一样，信息获取依然受到一系列因素的阻碍，包括技术限制、不平衡的服务交付、协调失败、以及妨碍公众知情权的有效法律限制。 Abstract : Gobernando la "edad de oro de la infraestructura": Evaluando las innovaciones de transparencia en el desarrollo de infraestructura de Filipinas: En medio de la creciente inversión en infraestructura en toda la región de Asia y el Pacífico, los notables déficits de responsabilidad han generado dudas sobre la capacidad de los gobiernos para contener la corrupción en el desarrollo de infraestructura en la región. Sin embargo, desarrollos recientes en Filipinas indican la presencia de desafíos relacionados con medidas de transparencia digitalmente mejoradas para salvar tales déficits de responsabilidad. Este artículo presenta el énfasis cambiante en las reformas de transparencia y rendición de cuentas relacionadas con el desarrollo de la infraestructura de Filipinas a partir de la década de 1990 y evalúa las innovaciones en transparencia bajo la administración de Duterte. Si bien las medidas importantes como el establecimiento de una plataforma electrónica de libertad de información han proporcionado un acceso conveniente a la información pública, aún existen obstáculos importantes para obtener documentos críticos sobre proyectos de infraestructura. Como se confirmó en un ejercicio para solicitar los estudios de viabilidad de 48 proyectos emblemáticos de infraestructura, el acceso a la información todavía está obstruido por factores que van desde limitaciones técnicas, prestación de servicios desiguales, fallas de coordinación, así como restricciones legales activas contra el derecho del público a saber.